SELF-REGULATED LEARNING SKILLS ENHANCEMENT - Sirazieva, Liliya; Zamaletdinov, Radif; Fahrutdinova, Rezida (Revista Inclusiones, 2018)
Self-regulated learning (SRL) is viewed as an important aspect of student academic performance and achievement. The aim of our research was to study, measure and enhance students selfregulated learning skills. Additionally, a certain learning environment and a training program were to be created. The participants in this study were 104 first year university students at the Kazan Federal University, the Institute of International Relations, History and Oriental Studies. Data were gathered twice by administering the Motivated Strategies for Learning Questionnaire (MSLQ), before and after the intervention. The intervention was focused on enhancing SRL skills within a period of 9 months. The results showed that the mean scores in the treatment group improved after the interventions, while mean scores in the control group remained practically on the same level. Summarizing the results, we can affirm that the interventions had an effect on SRL. The interventions included promotion of cognitive, metacognitive, and/or motivational strategies and focus on strategy application or benefit.